Membranous nephropathy PLA2R+ associated with Chagas disease - José Cândido Caldeira Xavier-Júnior; Vanessa dos Santos Silva; Rosa Marlene Viero (University of São Paulo, 2015)
Chagas disease (CD) - a tropical parasitic disease caused by the protozoan Trypanosoma cruzi - is a major health problem in Latin America. The immune response against the parasite is responsible for chronic CD lesions. Currently, there are no reports of an association between CD and membranous nephropathy (MN). The detection of the phospholipase A2 receptor (PLA2R) as a target antigen in idiopathic MN can improve the differential diagnosis of primary and secondary forms of MN. The authors report the case of a male patient with positive serology for CD who presented sudden death and underwent autopsy. Histological sections of the heart showed multifocal inflammatory infiltrate composed mainly of mononuclear cells, leading to myocardiocytes necrosis and interstitial fibrosis. The kidneys showed a MN with positive expression for PLA2R. As far as we know, this is the first report of a case of primary MN in a patient with CD, with severe chronic cardiomyopathy and heart failure.